2018
DOI: 10.3390/e20110841
|View full text |Cite
|
Sign up to set email alerts
|

Subnational Analysis of Economic Fitness and Income Dynamic: The Case of Mexican States

Abstract: In recent years, analytical tools of network theory have provided strong empirical support to the well-known hypothesis that regions develop through the local learning of capabilities (tacit productive knowledge). In this paper, we compare two indexes of competitiveness (or accumulated capabilities) for a subnational database of 32 Mexican states in the period 2004–2014. We find that Endogenous Fitness (i.e., region fitness and product complexity are derived jointly using only a Mexican exports database) has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…To analyze the effect of fiscal management performance on local development, we make use of GDP per capita as an indicator of economic development. Although there are criticisms regarding the use of this indicator (Acemoglu et al, 2001), it is widely used because of the practicality, simplicity and universality of its measure (see, for example, Bin and Peng, 2018;Castañeda and Romero-Padilla, 2018;Droller, 2018). The IBGE provides estimates for the GDP of the Brazilian municipalities from 2000 to 2015 (annual frequency) and population of each municipality.…”
Section: Data and The Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the effect of fiscal management performance on local development, we make use of GDP per capita as an indicator of economic development. Although there are criticisms regarding the use of this indicator (Acemoglu et al, 2001), it is widely used because of the practicality, simplicity and universality of its measure (see, for example, Bin and Peng, 2018;Castañeda and Romero-Padilla, 2018;Droller, 2018). The IBGE provides estimates for the GDP of the Brazilian municipalities from 2000 to 2015 (annual frequency) and population of each municipality.…”
Section: Data and The Methodologymentioning
confidence: 99%
“…Besides the variables mentioned above, taking into account the literature on economic development, which uses GDP per capita as a proxy, we use the following control variables in the models: WAGEformal workers' average wage (municipalitymonthly base). There is evidence, which suggests that a society with individuals capable of earning larger incomes on Fiscal management performance average tends to be more developed (see Castañeda and Romero-Padilla, 2018;Droller, 2018;Acemoglu et al, 2001). Formal worker's average wage data are available from the IBGE (Central Business Register).…”
Section: Data and The Methodologymentioning
confidence: 99%
“…Euclidean distance of the Mcp values between each city pair is calculated, and links are generated if the distance value falls below a given threshold. Across different years, it has been found that city pairs sharing similar distribution patterns exhibit a slight decreasing trend, with 24 links in 2000, 17 In general, Figure 1 shows that PRD cities are moving away from c1 (agriculture, forestry, livestock, fisheries), while shifting the focus towards c6 (finance), c7 (real estate), and c3 (building and construction). Such findings suggest that during the rapid-growth phase of PRD cities, the agricultural industry is the least economically sustainable sector, whereas finance, real estate, and building and construction are the most economically sustainable sectors.…”
Section: Economic Complexity In the Pearl River Delta Regionmentioning
confidence: 95%
“…Euclidean distance of the M cp values between each city pair is calculated, and links are generated if the distance value falls below a given threshold. Across different years, it has been found that city pairs sharing similar distribution patterns exhibit a slight decreasing trend, with 24 links in 2000, 17 Figure 3 shows the geographical distribution of economic complexity of the city cluster. Hong Kong-together with two super-cities, Shenzhen and Guangzhou and their surrounding cities-have formed a cluster that exhibits a high concentration in combined economic complexity.…”
Section: Economic Complexity In the Pearl River Delta Regionmentioning
confidence: 99%
See 1 more Smart Citation